TEORES DE COMPOSTOS BIOATIVOS E ATIVIDADE ANTIOXIDANTE DAS FOLHAS E CASCAS DE Eugenia dysenterica (MART.) DC. (MYRTACEAE) - LOPES, Emily Kamila de Souza; SILVA, Ana Francisca Gomes; BATISTA-SILVA, Valérioa Flávia (ANAIS DO ENIC, 2024)
-